Amphotericin B Encapsulation in Polymeric Nanoparticles: Toxicity Insights via Cells and Zebrafish Embryo Testing - Magno Maciel-Magalhães; Renata Jurema Medeiros; Nayara Cecília do Couto Guedes; Thais Morais de Brito; Gabriele Fátima de Souza; Beatriz Rodrigues Canabarro; Fausto Klabund Ferraris; Fábio Coelho Amendoeira; Helvécio Vinicius Antunes Rocha; Beatriz Ferreira de Carvalho Patricio; Isabella Fernandes Delgado (Pharmaceutics)
Background: Amphotericin B (AmB) is a commonly utilized antifungal agent, which is also recommended for the treatment of certain neglected tropical diseases, including leishmaniasis. However, its clinical application is constrained because of its poor oral bioavailability and adverse effects, prompting the investigation of alternative drug delivery systems. Polymeric nanoparticles (PNPs) have gained attention as a potential drug delivery vehicle, providing advantages such as sustained release and enhanced bioavailability, and could have potential as AmB carriers. However, concerns persist regarding nanomaterials’ toxicity, requiring more studies. Zebrafish (Danio rerio) embryos were used as a valuable model for toxicity testing, especially because of their genetic similarity to humans and standardized developmental assessments. Methods: In this study, we produced and characterized AmB loaded and non-loaded PNPs by nanoprecipitation, dynamic light scattering, transmission electron microscopy, atomic force microscopy and spectroscopy. Afterwards, we verified their toxicity through in vitro MTT assays in three cell lines (HEK293, HepG2, and J774 A1) and in vivo tests with zebrafish embryos. Results: In both trials, it was noted that nanoencapsulation of the drug led to increased toxicity when compared to non-encapsulated AmB, possibly indicating that they penetrated the embryo’s chorion. Nevertheless, it was demonstrated that the polymers used are safe and they are not the cause of toxicity, neither are the nanostructures per se. Conclusions: Therefore, it is believed that the objective of improving the bioavailability of AmB may have been achieved, and the observed toxicity was probably linked to AmB’s ability to destabilize cell membranes.